2019
DOI: 10.1111/cid.12872
|View full text |Cite
|
Sign up to set email alerts
|

Full‐zirconia single‐tooth molar implant‐supported restorations with angulated screw channel abutments: A 1‐year prospective case series study

Abstract: Background Implant‐supported restorations in the posterior region are subjected to various complications that could be prevented by changing either the design or the material. Purpose The aim of this prospective case series study was to evaluate full‐zirconia implant‐supported restorations with angulated screw channel abutments in the molar region of the maxilla and mandible and their effect on hard and soft peri‐implant tissues, during a 1‐year follow‐up period. Materials and Methods Thirty consecutive patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 24 publications
8
18
0
Order By: Relevance
“…No significant difference of MBL between the AG and CG was observed during the 1-year observation period (0.17 ± 0.39 mm vs. 0.19 ± 0.32 mm, p = 0.833). Similar results have been reported in previous studies, 22,34 where the MBL of angulated screw-retained restorations ranged from 0.16 to 0.41 mm, respectively. This indicates that both angulated screw-retained and cemented implant restorations can achieve stable marginal bone level in the short term.…”
Section: Discussionsupporting
confidence: 91%
“…No significant difference of MBL between the AG and CG was observed during the 1-year observation period (0.17 ± 0.39 mm vs. 0.19 ± 0.32 mm, p = 0.833). Similar results have been reported in previous studies, 22,34 where the MBL of angulated screw-retained restorations ranged from 0.16 to 0.41 mm, respectively. This indicates that both angulated screw-retained and cemented implant restorations can achieve stable marginal bone level in the short term.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 42 implants out of 49 required ASC abutments, based on surgical technique due to bone availability and probably laboratory technician design considerations. Another prospective study was presented by Pol et al 10 with ASC in the posterior region for single‐tooth molar rehabilitation. This prospective study consisted of 30 implants placed in the posterior maxilla and mandible followed by restoration with full contour zirconia restorations with ASC abutments.…”
mentioning
confidence: 99%
“…Only a few in vivo reports have reported on these restorations, and their results hint that this system can provide satisfying success and survival rates, even if at short follow-ups [21,29].…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical reports have reported on the efficacy of ASC in single crowns (SC) and Fixed Partial Dentures (FPD), but these preliminary results show that these restorations, even if at a 1 year follow-up [21,22], can provide a satisfactory result. Some in vitro studies have reported that as the channel is not perpendicular to the implant, which may receive off-axis loading, the rate of mechanical complications could possibly be higher than conventional, screw-retained, FPD.…”
Section: Introductionmentioning
confidence: 99%